Customary Right On The Sea By International Law Of The Sea Perspective Related To The Law Number 5 OF 1960 - Atmika Juresta Amira; Adhitya Nini Rizki Apriliana (Jurnal IUS Kajian Hukum dan Keadilan, 2020)
There are group of communities which still applied the customary law that has an impact to the emerge of the right which is the form consequence of the appliance of customary law, named customary right. The order of customary law ruled that land is handed over by the manager and its use to each of the existing tribes. This custom has been hereditary for a long time. Law Number 5 of 1960 concerning Regulations of Agraria states that the state basically provides protection for the embodiment of customary rights and rights which are similar to the customary rights of customary law communities, as long as in practice there are still conditions for the implementation of these rights. Conception of customary rights as applied in land areas is basically also known by international law of the sea in terms of traditional fisheries rights. However, UNCLOS 1982 on this case does not regulate specifically about the rights of the customary rights on the sea but only regulates the position of the community especially the fishing community to contribute with the government in the management and use of the sea on its territory. This research is juridical normative research that uses a statute approach and conceptual approach. This study aims to find out how the enforcement of customary rights on the sea area through the perspective of international law of the sea considering the sea area is an area whose boundaries must be agreed upon by countries under international law instruments.